2017
DOI: 10.1016/j.desal.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Integrating membrane distillation with waste heat from natural gas compressor stations for produced water treatment in Pennsylvania

Abstract: Direct contact membrane distillation (DCMD) has immense potential in the desalination of highly saline wastewaters where reverse osmosis is not feasible. This study evaluated the potential of DCMD for treatment of produced water generated during extraction of natural gas from unconventional (shale) reservoirs. Exhaust stream from Natural Gas Compressor Station (NG CS), which has been identified as a potential waste heat source, can be used to operate DCMD thereby providing economically viable option to treat h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…Lokare et al [114] investigated the synergies and potential of DCMD for wastewater treatment produced during gas extraction from unconventional (shale) reservoirs in Pennsylvania (PA).…”
Section: Application Of MDmentioning
confidence: 99%
See 1 more Smart Citation
“…Lokare et al [114] investigated the synergies and potential of DCMD for wastewater treatment produced during gas extraction from unconventional (shale) reservoirs in Pennsylvania (PA).…”
Section: Application Of MDmentioning
confidence: 99%
“…A comprehensive cost evaluation of a 111 MWe solar power tower (SPT) plant integrated with the DCMD system was investigated by Soomro and [114,175]. The average freshwater production by the proposed MD system was evaluated up to 40,759 L/day with a cost of $0.392/m 3 .…”
Section: Economic Analysis Of MD Processmentioning
confidence: 99%
“…Following the disciplines outlined above, we have selected four solvents for PVDF membrane fabrication by TIPS method, the parameters of which were listed in (8)(9) and DOP (5.3), DOA (4)(5) and DOS (<4) demonstrated a great difference in polarity. Therefore, the poor compatibility between PVDF and the other three solvents were characterized and listed in Table 1.…”
Section: Binary Diluent Determinationmentioning
confidence: 99%
“…4 Among the membrane materials applied in the MD process, semi-crystalline polyvinylidene uoride (PVDF) has attracted much attention owing to its notable chemical stability, stain resistance, mechanical properties, wide processing temperature, and pliability.…”
Section: Introductionmentioning
confidence: 99%
“…The p-CSM showed an effective Cu 2+ adsorption capacity of 2.57 mmol/g, and an adsorption efficiency of 90% for Cu 2+ could be maintained even after six cycles. Polyethersulfone-Titania organicinorganic hollow fiber hybrid membrane was prepared by sol-gel process assisted reverse physically induced phase separation, and the organic-inorganic hybrid membranes exhibited good performance with a maximum pure water flux of 1046 L/m 2 ·h.Membrane distillation.Exhaust stream from natural gas compressor station (NGCS) was identified as a potential waste heat source, which can be used to operate direct contact membrane distillation, thereby providing economically viable option for processing high salinity produced water(Lokare et al, 2017). Energy analysis showed that the waste heat available from NGCS was sufficient to concentrate all the produced water generated in Pennsylvania to 30 wt.% Yang et al (2017).…”
mentioning
confidence: 99%